Acceptance, efficacy, and safety of COVID-19 vaccination in older patients with cancer. Issue 6 (July 2022) - Couderc, Anne-Laure; Ninove, Laetitia; Nouguerède, Emilie; Rey, Dominique; Rebroin, Marina; Daumas, Aurélie; Tomasini, Pascale; Greillier, Laurent; Salas, Sebastien; Duffaud, Florence; Dahan, Laetitia; Duluc, Muriel; et al.
Abstract: Purpose: The COVID-19 vaccination campaign began in December 2020, in France, and primarily targeted the oldest people. Our study aimed to determine the level of acceptance of vaccination in a population of older patients with cancer. Methods: From January 2021, we offered vaccination with the BNT162b2 COVID-19 vaccine to all patients 70 years and older referred to our geriatric oncology center in Marseille University Hospital (AP-HM) for geriatric assessment before initiation of an oncological treatment. Objectives were to evaluate acceptance rate of COVID-19 vaccination and to assess vaccine safety, reactogenicity, and efficacy two months after the first dose. Results: Between January 18, 2021 and May 7, 2021, 150 older patients with cancer were offered vaccination after a geriatric assessment. The majority were men (61.3%), with a mean age of 81 years. The two most frequent primary tumors were digestive (29.4%) and thoracic (18%). The vaccine acceptance rate was 82.6% and the complete vaccination rate (2 doses) reached 75.3%. Among the vaccinated patients, 15.9% reported mild side effects after the first dose and 23.4% after the second dose, mostly arm pain and fatigue. COVID-19 cases were observed in 5.1% of vaccinated patients compared with 16.7% in unvaccinated patients. Of the 22 vaccinated patients who agreed to have their serum tested, 15 had antibodies against the spike protein at day 21 after the first dose. Conclusion: Our study showed a high acceptance rate of COVID-19 vaccination, with good tolerance in this frail population. These results highlight the benefits of organizing vaccination campaigns at the very beginning of oncological management in older patients. Clinical trial registration : This study was registered May 23, 2019 in ClinicalTrials.gov (NCT03960593 ).